Web-based counseling system / Avinash Pratap Ramasamy - Avinash Pratap, Ramasamy (2002)
As we know that the advancement of information technology and increasing numbers of users getting connected to the internet, different promotional methods are employed on the wold wide web (www). Providing sufficient information, so as to entice to user to visit the property. Effects of the technological developments in the counseling scope and the fruits of applied technology with the main factor of economic force. Profit motives that are always behind the scenes regulating the flows and rates of implementation has shape the relative popularity and growth patterns of competing, usually interdependent and products· Therefore value added services such as providing the onlinc counseling services for students or users will be beneficial to the institutes, colleges, varsities and schools. This project will be focused on developing a web based counseling system that will be deployed within tile website of institutes or educational, organizations in the Internet as to provide the service an value added service feature and the capability in an online schools, varsities, colleges systems that has not been developed such a feature but still practicing the conventional way. The main consideration in this project is implementing the easy way of counseling which could ease of use, cost minimizing and it would be personal and manageability.